Measuring customer satisfaction on the cleanliness of food premises using fuzzy conjoint analysis: a pilot test - Lim, Sook Yee; Harun, Ummilia Balqis; Gobil, Abdul Rahman; Mustafa, Noor Afiqah; Zahid, Nur Azwanis; Nordin, Syafinaz Amin; Md. Ariffin, Umi Kalsom; Tengku Jamaluddin,, Tengku Zetty Maztura; Mohamed, Nurul Azmawati; Mohd Zulkefli, Nor Afiah; Shohaimi, Shamarina (Public Library of Science, 2021)
Determining the level of customer satisfaction in cleanliness regarding a product or service is a significant aspect of businesses. However, the availability of feedback tools for consumers to evaluate the cleanliness of a restaurant is a crucial issue as several aspects of cleanliness need to be evaluated collectively. To overcome this issue, this study designed a survey instrument based on the standard form used for grading the food premises and transformed it into a seven Likert scale questionnaire and consists of seven questions. This study employed fuzzy conjoint analysis to measure the level of satisfaction in cleanliness in food premises. This pilot study recruited 30 students in Universiti Teknologi MARA (UiTM) Seremban 3. The student’s perception was represented by the scores calculated based on their degree of similarities and corresponding levels of satisfaction, whereby, only scores with the highest degree of similarity were selected. Furthermore, this study identified the aspects of hygiene that assessed based on the customers’ satisfaction upon visiting the premises. The results indicated that the fuzzy conjoint analysis produced a similar outcome as the statistical mean, thus, was useful for the evaluation of customer satisfaction on the cleanliness of food premises.